Pulsatile flow of non-Newtonian blood fluid inside stenosed arteries: Investigating the effects of viscoelastic and elastic walls, arteriosclerosis, and polycythemia diseases. (February 2018) - Nejad, A. Abbas; Talebi, Z.; Cheraghali, D.; Shahbani-Zahiri, A.; Norouzi, M.
Highlights: The interaction of pulsatile blood flow with the viscoelastic artery is modeled. The modified Casson and generalized Maxwell are used as the constitutive equations. The effects of blood rheology on atherosclerosis and polycythemia are investigated. Abstract: Background and objective: In this study, the interaction of pulsatile blood flow with the viscoelastic walls of the axisymmetric artery is numerically investigated for different severities of stenosis. The geometry of artery is modeled by an axisymmetric cylindrical tube with a symmetric stenosis in a two-dimensional case. The effects of stenosis severity on the axial velocity profile, pressure distribution, streamlines, wall shear stress, and wall radial displacement for the viscoelastic artery are also compared to the elastics artery. Furthermore, the effects of atherosclerosis and polycythemia diseases on the hemodynamics and the mechanical behavior of arterial walls are investigated. Methods: The pulsatile flow of non-Newtonian blood is simulated inside the viscoelastic artery using the COMSOL Multiphysics software (version 5) and by employing the fluid-structure interaction (FSI) method and the arbitrary Lagrangian-Eulerian (ALE) method. Moreover, finite element method (FEM) is used to solve the governing equations on the unstructured grids. For modeling the non-Newtonian blood fluid and the viscoelastic arterial wall, the modified Casson model, and generalized Maxwell model are used, respectively. Results: According to the results, with stenosis severity increasing from 25% to 75% at the time of maximum volumetric flow rate, the maximum value of axial velocity and its gradient increase 7.9 and 19.6 times, and the maximum wall shear stress of viscoelastic wall increases 24.2 times in the constriction zone. With the progression of the atherosclerosis disease (fivefold growth of arterial elastic modulus), the wall radial displacement of viscoelastic arterial walls decreases nearly 40%. Conclusions: In this study, axial velocity profile, pressure distribution, streamlines, wall radial displacement, and wall shear stress were examined for different percentages of stenosis (25%, 50%, and 75%). The atherosclerosis disease was investigated by the fivefold growth of viscoelastic arterial elastic modulus and polycythemia disease was examined by the 21-fold increase in the yield stress of the blood fluid. Furthermore, the comparison of results between the elastic and viscoelastic arterial walls shows that the wall radial displacement for viscoelastic artery is lower than that for the elastic artery as much as 21.7% for the severe stenosis of 75%.